MOJANG JAJAKA SEBAGAI BAGIAN DARI MARKETING PUBLIC RELATIONS DALAM MEMPROMOSIKAN PARIWISATA DAN BUDAYA KOTA BOGOR - Kiki Rizqi Sofia; Ispawati Asri (Ikon --Jurnal Ilmiah Ilmu Komunikasi, 2021)
Bogor City has interesting tourism potential, including natural, cultural and culinary tourism. In fact, Bogor previously became the most loved city in the world in The We Love Cities 2016 campaign and the award called ‘The Most Lovable City’. With all those advantages Bogor City can be introduced to all regions in Indonesia and abroad. And to make it happened, it requires the role of a tourism ambassador to promote its potential tourism. This study aims to determine the role of the Mojang Jajaka in promoting tourism potential of Bogor City. And knowing the efforts and obstacles that passed in carrying out the action. This research uses The Role of Public Relations and Public Relations Mix Theory. The method used is descriptive qualitative and data collection techniques using in-depth interviews, documentation, and literature study. The results showed that the Mojang Jajaka runs its role as part of marketing public relations in promoting the tourism potential of the Bogor City, and supported by the efforts that have been carried out.